Identifikasi Molekuler dan Potensi Bakteri Endofit dari Tanaman Combretaceae - Parapat, Timothy Samuel; Prasetya, Eko (Mahesa Research Center, 2025)
Plants from the Combretaceae family are known as medicinal plants, some of which are the genera Combretum and Terminalia. Ketapang (Terminalia catappa) is one of the plants from the genus Combretaceae that can produce beneficial metabolite compounds. In addition to being useful in increasing plant growth, endophytic bacteria have the ability to produce the same metabolites as their host plants. This study aims to identify endophytic bacterial species found in plants of the Combretaceae family and to examine their potential. The methods used in this study are identification of the characteristics of endophytic bacterial cells using a light microscope, molecular identification through the BLAST program, and literature studies. The results of this study are 9 species of endophytic bacteria associated with plants from the Combretaceae family. They are Lysinibacillus fusiformis, Citrobacter freundii, Staphylococcus epidermidis, Enterobacter cloacae, Pseudomonas fulva, Bacillus subtilis, Staphylococcus hominis, Paenibacillus motobuensis, Cronobacter sakazakii, Cytobacillus firmus, and Methylobacterium radiotolerants.